Thin film material, preparation method thereof, interconnection structure and chip

通过在芯片制程中使用等离子体增强原子层沉积技术,以有机钽为前驱体制备的钽、碳和氮元素含有的薄膜材料,解决了现有技术中难以高效制备金属Ta黏附层的问题,实现 High-quality, low-corrosive film preparation and good adhesion and barrier properties.

CN119447093APending Publication Date: 2025-02-14HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310949151.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently, quickly and with high quality preparation of metal Ta adhesive layers, which limits the application of tantalum metal films in advanced chip manufacturing processes.

Method used

Using plasma enhanced atomic layer deposition (PEALD) technology, using organic tantalum as the precursor, thin film materials are prepared by plasma deposition method, which include tantalum, carbon and nitrogen elements and are free of halogen.

Benefits of technology

A high-quality, low-corrosive tantalum metal film preparation is achieved, which improves the adhesion performance to the interconnection layer copper and the barrier layer tantalum nitride, and enhances the barrier performance to Cu.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447093A_ABST
    Figure CN119447093A_ABST
Patent Text Reader

Abstract

The invention provides a thin film material, a preparation method thereof, an interconnection structure and a chip. The thin film material comprises a tantalum element, a carbon element and a nitrogen element, the thin film material does not contain halogen, the atomic percent of the tantalum element in the thin film material is greater than 70%, the atomic percent of the carbon element in the thin film material is 0.1-7%, and the atomic percent of the nitrogen element in the thin film material is 0.1-4%. The thin film material can be used as an adhesive material for an interconnection layer and a barrier layer of a chip so as to improve the adhesion and barrier property between the interconnection layer and the barrier layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor materials, and in particular to a thin film material and a preparation method thereof, an interconnection structure, and a chip. Background Art

[0002] Tantalum (Ta) metal is one of the most widely used adhesion materials for Damascus copper interconnect technology in integrated circuits. Ta metal can effectively improve the adhesion between copper interconnects and tantalum nitride (TaN) barrier layers due to its good adhesion. In conventional processes, tantalum metal films are deposited by physical vapor deposition (PVD). However, as the width of chip interconnects continues to shrink, PVD technology can no longer meet the development of advanced interconnect processes.

[0003] Compared with traditional PVD thin film preparation technology, atomic layer deposition (ALD) technology can accurately control the thickness and composition of the film at the sub-nanometer scale, and the grown film has better conformality and uniformity, which is suitable for the growth of thin film materials on advanced interconnect structures. In addition, in the back-end process of the chip, the temperature of film growth cannot exceed 400°C. Since the deposition temperature of the film can be effectively reduced in the plasma-assisted atmosphere, plasma enhanced atomic layer deposition (PEALD) technology is more suitable for chip interconnection processes, especially the preparation of barrier layer and adhesion layer materials in advanced interconnections. However, even with the use of PEALD technology, how to efficiently, quickly and with high quality prepare the metal Ta adhesion layer has not yet been overcome by the industry and academia, which also restricts the application of tantalum metal films in advanced chip processes. Summary of the invention

[0004] The present application provides a thin film material and a preparation method thereof, an interconnection structure, and a chip, so as to provide an adhesive material which is non-corrosive, has a certain barrier property to Cu, and has a high bonding property with an interconnection layer.

[0005] In a first aspect, the present application provides a thin film material, which includes tantalum, carbon and nitrogen, and the thin film material does not contain halogen, wherein the atomic percentage of the tantalum element in the thin film material is greater than 70%, the atomic percentage of the carbon element in the thin film material is 0.1 to 7%, and the atomic percentage of the nitrogen element in the thin film material is 0.1 to 4%.

[0006] The main element of the thin film material of the present application is tantalum. The tantalum in the thin film material has high adhesion to the copper of the interconnection layer, and also has high adhesion to the tantalum nitride of the barrier layer. The thin film material of the present application does not contain halogens. When the thin film material contacts the metal in the interconnection layer of the chip, it will not corrode the interconnection layer, thereby avoiding the reduction of the connection strength between the thin film material and the interconnection layer due to the corrosion of halogens. In addition, by including 0.1-7% carbon and 0.1-4% nitrogen, the barrier performance of the thin film material to Cu can be further improved without significantly reducing the conductive performance of the thin film material and while ensuring the adhesion between the thin film material and the interconnection layer.

[0007] In an optional implementation, the total atomic percentage of the carbon element and the nitrogen element is less than 10%. The total atomic number of the carbon element and the nitrogen element should not be too large, as too much will easily cause the conductivity of the thin film material to decrease, and when used in an interconnect structure, it will cause the electrical performance of the semiconductor device to decrease.

[0008] Exemplarily, the atomic ratio of the carbon element to the tantalum element may be less than 0.1, such as less than or equal to 0.08. Exemplarily, the atomic ratio of the nitrogen element to the tantalum element may be less than 0.06, such as less than or equal to 0.05. When the atomic ratio of the carbon element to the tantalum element is too high and the atomic ratio of the nitrogen element to the tantalum element is too high, the conductivity of the film material will decrease. Therefore, by limiting the ratio of the number of atoms of the carbon element and the nitrogen element to tantalum in the film material, the barrier performance of the film material can be effectively improved while ensuring that the film material has good adhesion and good conductivity.

[0009] In a second aspect, the present application provides a method for preparing a thin film material, wherein the method uses organic tantalum as a precursor to perform plasma deposition to prepare the thin film material; wherein the organic tantalum contains carbon and nitrogen.

[0010] The thin film material obtained by the preparation method of the present application may have the same performance as the thin film material of the first aspect of the present application. The corresponding effect description in the first aspect above can be referred to, and the performance of the thin film material obtained by the method will not be repeated here. In addition, the preparation method of the present application uses organic tantalum as a precursor and is obtained by plasma deposition, such as plasma enhanced atomic layer deposition. The preparation method can significantly improve the preparation rate of tantalum metal film, and the prepared thin film material can have high uniformity and conformality. The preparation method is compatible with the current chip manufacturing process, for example, it is compatible with the preparation process of TaN, without the need to add additional process equipment, reducing the manufacturing difficulty and processing cost.

[0011] In an optional implementation, at least one of Ta(NR1R2)5 or R3N=Ta(NR4R5)3, R1 to R5 are each independently selected from a C1 to C5 alkyl group. Exemplarily, R1 to R5 are each independently selected from a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group or a tert-amyl group or one of their isomers.

[0012] In an optional implementation, a discharge gas is introduced as a co-reactant in the plasma deposition, and the discharge gas includes hydrogen and argon, and the flow ratio of the hydrogen to the argon is greater than 0 and less than 3. Since the preparation method of the present application uses organic matter as a precursor, experiments have shown that when a mixed gas of hydrogen and argon is used as a co-reactant to generate plasma, the carbon and nitrogen contents in the thin film material can be effectively reduced to be controlled within the range defined in the present application.

[0013] During the plasma deposition process, the organic tantalum can be heated to 70-100°C, and argon gas is used as a carrier gas to load the saturated vapor of the organic tantalum into the reaction chamber of the deposition equipment for a time greater than 2s; a mixed gas of hydrogen and argon is used as a discharge gas, and the gas flow rates are 25-100sccm and 0-75sccm respectively, the discharge mode is capacitively coupled plasma, the discharge duration is 5-30s, the discharge power is 50-200W, and the frequency is less than 15MHz. Repeat the above process, and a thin film material of the desired thickness is obtained after a deposition cycle.

[0014] In a third aspect, the present application provides an interconnection structure, which includes an interconnection layer, an adhesion layer and a barrier layer, wherein the adhesion layer is located between the interconnection layer and the barrier layer, the interconnection layer is a copper layer, and the adhesion layer is a thin film material in the first aspect and any optional implementation thereof. The adhesion layer is used to enhance the bonding strength between the interconnection layer and the barrier layer to prevent the interconnection layer from peeling off.

[0015] In an optional implementation, the thickness of the adhesion layer may be less than or equal to 20 nm.

[0016] In a fourth aspect, the present application provides a chip, comprising the interconnection structure in the third aspect and any optional implementation thereof.

[0017] The technical effects that can be achieved by the third to fourth aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here.

[0018] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the atomic number ratio of tantalum element, the atomic number ratio of carbon element, the atomic number ratio of nitrogen element, the thickness of the adhesion layer and other data, when measuring, the values ​​within the scope of engineering measurement error should be understood to be within the scope specified in the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a schematic diagram of a Damascus interconnect structure according to an embodiment;

[0020] Figure 2 A schematic diagram of a deposition process;

[0021] Figure 3 It is the XPS test result figure of the samples of different embodiments;

[0022] Figure 4 It is a TDDB test model diagram of the samples of the embodiment and the comparative example;

[0023] Figure 5 It is a test diagram of the time when different samples of Example 1 and Comparative Example 2 undergo breakdown under constant pressure conditions;

[0024] Figure 6 This is a SEM image of the groove of the sample of Example 1.

[0025] Reference numerals:

[0026] 11 -interconnection layer; 12 -adhesion layer; 13 -barrier layer; 21 -Si substrate; 22 -SiO2 dielectric layer; 23 -Ta thin film layer; 24 -copper layer. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0028] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0029] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0030] As the size of integrated circuits continues to decrease, the metal wiring inside the chip is becoming thinner and thinner, and the layers are increasing. In order to reduce the signal crosstalk and RC delay of integrated circuits, copper wires with lower resistivity are often used to replace traditional aluminum wires to form metal interconnect layers to form Damascus interconnect structures. Figure 1 FIG. 1 is a schematic diagram of a Damascus interconnect structure of an embodiment. Figure 1 As shown, the Damascus interconnect structure includes a copper layer as an interconnect layer 11. In order to prevent the diffusion of copper in the dielectric layer of the chip, a barrier layer 13 is usually covered on the surface of the copper layer to prevent copper atoms and copper ions from diffusing into the dielectric layer and causing chip failure. Since tantalum nitride is relatively stable, tantalum nitride is usually used as the barrier layer 13 of the copper layer. In order to improve the adhesion between the interconnect layer 11 and the barrier layer 13, a tantalum metal layer is usually provided between the two as an adhesion layer 12.

[0031] The embodiment of the present application provides a thin film material, which mainly includes tantalum, carbon and nitrogen. The thin film material can be used in the Damascus interconnection structure of the chip, such as being arranged between the copper layer interconnection layer and the tantalum nitride barrier layer. By arranging the thin film material, the bonding strength between the copper layer and the tantalum nitride can be improved, and the blocking force on the copper layer can be improved, preventing the probability of the copper layer passing through the thin film material and entering the dielectric layer of the chip, thereby improving the stability and reliability of the metal connection in the interconnection structure. The thin film material will be further described in detail below.

[0032] The thin film material of the embodiment of the present application includes tantalum, carbon and nitrogen. Carbon can form tantalum carbide with tantalum, and nitrogen can form tantalum nitride with tantalum. In addition, the thin film material may also include oxygen. Among them, the atomic percentage of tantalum in the thin film material is greater than 70%. Among them, the atomic percentage is the percentage of atomic number. Tantalum metal can effectively improve the adhesion between the copper interconnect layer and the tantalum nitride barrier layer due to its good adhesion, which mainly improves the bonding strength between the two and prevents the copper layer from falling off. Exemplarily, the atomic percentage of tantalum in the thin film material may be 70%, 75%, 80%, 85% or 90% or more.

[0033] The atomic percentage of carbon in the film material is 0.1-7%. For example, the atomic percentage of carbon in the film material can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6% or 7% or any value between the above two values.

[0034] The atomic percentage of nitrogen in the film material is 0.1-4%. The addition of nitrogen can further improve the barrier performance of the film material to copper, thereby further improving the stability of the chip structure. Exemplarily, the atomic percentage of nitrogen in the film material can be, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5, 3%, 3.5% or 4% or a value between any two of the above values.

[0035] The film material does not contain halogens. The presence of halogens makes the film material very susceptible to moisture in the air, causing slow decomposition, thereby affecting the life of the film material.

[0036] In an optional embodiment, in the thin film material, the total atomic number of carbon and nitrogen elements accounts for less than 10%. Among them, the atomic ratio of carbon and tantalum is less than 0.1. The atomic ratio of nitrogen and tantalum is less than 0.06. If the total atomic number of carbon and nitrogen elements is too high, or the atomic ratio of any element of carbon or nitrogen to tantalum is too high, it will affect the conductivity of the thin film material, and then affect the electrical performance of the chip. Exemplarily, in the thin film material, the total atomic ratio of carbon and nitrogen elements can be, for example, 9%, 8%, 7%, 6%, 5%, 4%, 3% or 2% or a value between any two of the above values. The atomic ratio of carbon and tantalum can be, for example, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01 or a value between any two of the above values. The atomic ratio of nitrogen to tantalum may be, for example, 0.05, 0.04, 0.03, 0.02, 0.01 or any value between any two of the above values.

[0037] The thin film material of the embodiment of the present application can be prepared by using organic tantalum as a precursor and by a plasma deposition method, wherein the organic tantalum contains carbon and nitrogen.

[0038] Wherein, the organic tantalum may include at least one of Ta(NR1R2)5 or R3N=Ta(NR4R5)3, R1, R2, R3, R4 and R5 are each independently selected from C1 to C5 alkyl groups, and illustratively, R1, R2, R3, R4 and R5 are each independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl or tert-amyl, or one of the isomers of tert-amyl. Exemplarily, the organic tantalum includes but is not limited to at least one of the compounds shown in the following structural formula:

[0039]

[0040]

[0041] The plasma deposition used in the preparation method of the embodiment of the present application may be plasma enhanced atomic layer deposition, and the discharge mode of the plasma deposition may be a capacitively coupled plasma mode.

[0042] In the deposition process, in addition to introducing organic tantalum as a precursor to form a thin film material, a mixed gas of hydrogen and argon can also be introduced as a co-reactant. Hydrogen and argon can be used to generate plasma to provide free radicals and energy for the deposition reaction to promote the chemical reaction of organic tantalum to form tantalum metal. In this process, since organic tantalum contains certain carbon and nitrogen elements, after plasma deposition, carbon and nitrogen elements are deposited in the thin film material.

[0043] In the mixed gas of hydrogen and argon, the flow ratio of the hydrogen to the argon is greater than 0 and less than 3. By introducing a certain amount of argon, the contents of C and N in the thin film material can be reduced, so that the contents of C and N are maintained within a desired range.

[0044] Figure 2 Schematic diagram of a deposition process. Figure 2 The method for preparing the thin film material of the embodiment of the present application comprises the following steps:

[0045] S1, heating the organic tantalum to 70-100° C., using argon as a carrier gas, loading the saturated vapor of the organic tantalum into a reaction chamber of a deposition device, and depositing the organic tantalum on the surface of the substrate for a time greater than 2 seconds;

[0046] S2, using a mixture of hydrogen and argon as a purge gas for more than 10 seconds to remove organic tantalum and by-products that are not deposited on the deposition surface;

[0047] S3, using a mixture of hydrogen and argon as the discharge gas, with gas flow rates of 25-100 sccm and 0-75 sccm respectively, the discharge mode is capacitively coupled plasma, the discharge duration is 5-30 s, the discharge power is 50-200 W, and the frequency is less than 15 MHz;

[0048] S4, again using a mixture of argon and hydrogen as a purge gas for 20 to 40 seconds to remove reaction by-products;

[0049] S5, repeating steps S1 to S4 for several deposition cycles to obtain a thin film material of a desired thickness.

[0050] The thin film material of the present application is used as an adhesion layer between the interconnection layer and the barrier layer, and its thickness can be less than or equal to 20 nm.

[0051] The preparation method of the present application will be further described in detail below in combination with examples and comparative examples.

[0052] Example 1

[0053] The method for preparing the thin film material of this embodiment comprises the following steps:

[0054] S11, using TBTDET as a precursor, heating the precursor to 90° C., using argon as a carrier gas, loading the saturated vapor of the TBTDET precursor into the reaction chamber for 5 seconds to deposit the TBTDET precursor on the surface of the substrate;

[0055]

[0056] S12, using a mixture of hydrogen and argon as a purge gas for 30 seconds to remove the undeposited precursors and byproducts;

[0057] S13, using a mixture of hydrogen and argon as the discharge gas, with gas flow rates of 50 sccm and 10 sccm respectively, the discharge mode is capacitively coupled plasma, the discharge duration is 20 s, the discharge power is 110 W, and the frequency is 13.56 MHz;

[0058] S14, using argon-hydrogen mixed gas as purge gas again for 30 seconds to remove reaction by-products;

[0059] S15, repeating steps S11 to S14 for several deposition cycles to obtain a tantalum metal film of a desired thickness.

[0060] The thickness of the thin film material grown by cyclic growth for 100 times, 300 times and 600 times was tested respectively, and the test results are listed in Table 1.

[0061] Table 1

[0062]

[0063] The growth rate was fitted according to the film thickness corresponding to 100, 300 and 600 growth cycles. The fitting results are shown in Figure 2 See Figure 2 According to the fitting results, in the preparation method of the present application, the growth rate of the film is about

[0064] Example 2

[0065] The method for preparing the thin film material of this embodiment is different from that of embodiment 1 in that the flow rates of hydrogen and argon are different. In this embodiment, the flow rates of hydrogen and argon are 50 sccm and 50 sccm respectively, and the deposition cycle is 100 times. The rest is the same as embodiment 1.

[0066] The elements of different samples of Example 1 and Example 2 were detected by X-ray electron spectrometer XPS. The number of samples tested in Example 1 was 3. The number of samples in Example 2 was 1. The test results are listed in Figure 3 .

[0067] like Figure 3 As shown in the figure, the composition characterization results of the thin films prepared with TBTDET as the precursor and H2:Ar of 50sccm:10sccm show that the atomic percentage of Ta element is greater than 70%. For sample No. 1, the atomic percentage of Ta element is 78.46%, N is 1.11%, C is 4.47%, and O is 15.97%; for sample No. 2, the atomic percentage of Ta element is 75.42%, N is 2.13%, C is 4.03%, and O is 18.42%; for sample No. 3, the atomic percentage of Ta element is 70.84%, N is 1.84%, C is 2.58%, and O is 24.74%; for sample No. 4, the atomic percentage of Ta element is 74.24%, N is 1.70%, C is 4.89%, and O is 19.18%. Among them, all samples contain oxygen. In addition to the possibility that some oxygen may be introduced during the reaction process, the main reason is that the prepared Ta metal film is easily oxidized by air after being taken out of the reaction chamber of the deposition equipment. Therefore, the atomic percentage of oxygen element in the XPS characterization results is relatively high.

[0068] Example 3

[0069] The method for preparing the thin film material of this embodiment comprises the following steps:

[0070] S11, using PDEAT as a precursor, heating the precursor to 90°C, using argon as a carrier gas, loading the saturated vapor of the PDEAT precursor into the reaction chamber for 5 seconds;

[0071]

[0072] S12, using a mixture of hydrogen and argon as a purge gas for 30 seconds to remove unreacted precursors and by-products;

[0073] S13, using a mixture of hydrogen and argon as the discharge gas, with gas flow rates of 50 sccm and 10 sccm respectively, the discharge mode is capacitively coupled plasma, the discharge duration is 20 s, the discharge power is 110 W, and the frequency is 13.56 MHz;

[0074] S14, using argon-hydrogen mixed gas as purge gas again for 30 seconds to remove reaction by-products;

[0075] S15, repeating steps S11 to S14 for 100 deposition cycles to obtain a tantalum metal film of a desired thickness.

[0076] Comparative Example 1

[0077] Tantalum pentachloride (TaCl5) was used as a precursor to prepare thin film materials by plasma deposition.

[0078] Specifically, TaCl5 is used as a precursor and hydrogen plasma is used as a co-reactant. At a certain deposition temperature, Ta metal film is prepared in the interconnection process by plasma enhanced atomic layer deposition (PEALD), and the reaction formula is: TaCl5(s)+5H(g)→Ta(s)+5HCl(g).

[0079] Through testing, when TaCl5 is used as a precursor to prepare thin film materials, the growth rate of the thin film material is about This is mainly because the TaCl5 precursor can react with the deposited Ta film, and the by-product HCl is easily adsorbed on the Ta film, so the growth rate of the Ta film prepared by this method is relatively low.

[0080] By comparing the growth rates of Example 1 and Comparative Example 1, it can be seen that the use of organic tantalum to prepare tantalum film can significantly increase the growth rate of the film. Even under growth conditions that do not exceed the interconnection process temperature of 400°C, the rate of preparing tantalum film with an organic precursor is faster, thereby improving the efficiency of film preparation. In addition, the use of inorganic TaCl5 as a precursor, TaCl5 is highly corrosive and can easily damage the chamber and valves of the deposition equipment, making it difficult to apply to large-scale industrial production. In order to avoid damage, the gas path and pipeline need to be heated and precious metal electroplated, which increases the difficulty and cost of manufacturing.

[0081] The preparation method of the embodiment of the present application uses organic tantalum as a precursor, which is non-corrosive to the equipment and can avoid damage to the cavity and valve by the precursor. Since the preparation of TaN thin film is usually carried out by plasma deposition in the preparation process of the chip, the preparation method of the present application can be combined with the chip manufacturing process to avoid the introduction of new processing equipment.

[0082] Comparative Example 2

[0083] Tantalum thin films were prepared by PVD method.

[0084] Among them, multi-source integrated PVD equipment is used for deposition. During the deposition process, metal tantalum is directly used as a target to deposit tantalum on the substrate. The deposition power is 300W, the deposition rate is 10.4nm / min, the deposition pressure is 4mtorr, and the deposition time is 18s to obtain a tantalum film.

[0085] The films of Example 1 and Comparative Example 2 were subjected to a dielectric layer time-dependent breakdown test (TDDB), wherein the sample model of the TDDB test is shown in FIG. Figure 4 As shown, the Ta film 23 is deposited on the surface of the SiO2 dielectric layer 22 using the methods of each embodiment, wherein the SiO2 dielectric layer 22 is arranged on the surface of the Si substrate 21. The surface of the Ta film 23 is provided with a copper layer 24. The test method is as follows: voltage is applied to the copper layer 24 and the Si substrate 21, and the time to failure (TTF) at breakdown is detected under a constant electric field stress of 6.8 MV / cm. The TTF of multiple samples can be obtained by testing the TTF 50% .TTF 50% is the median failure time of different samples, indicating that the number of samples with a failure time less than this value is 50%, and the number of samples with a failure time greater than this value is also 50%.

[0086] Figure 5 is the time when different samples in Example 1 and Comparative Example 2 undergo breakdown under the above electric field. Figure 5 As shown, the TTF corresponding to the sample of Example 1 50% The TTF of the sample in comparative example 2 is 33.2s. 50% It is 19.4s. It is said that the tantalum metal film of the embodiment of the present application has significantly better barrier performance against copper interconnects than the tantalum metal film prepared by conventional PVD. This is mainly because the tantalum metal film of the embodiment of the present application contains trace amounts of C and N elements, and C and N exist in the film in the form of TaC and TaN compounds, respectively, and TaC and TaN have good barrier performance against copper metal. Therefore, the barrier performance of the film of the embodiment of the present application against copper metal is better than that of the Ta metal film prepared by PVD.

[0087] In addition, the thin film material is deposited on the surface of the groove of the substrate using the preparation method of Example 1. The groove width of the groove is less than 20 nm. The substrate slice after deposition is observed by SEM to observe whether there is metal tantalum deposition in the groove structure of the substrate. The SEM test picture is as follows: Figure 6 As shown. Among them, Figure 6 (a) is a schematic diagram of the structure in the trench of the substrate. Figure 6 (b) is a partial enlarged view of the bottom of the groove in (a). Figure 6 (c) is a partial enlarged view of the groove wall in (a). Figure 6 , a tantalum metal film with good uniformity and high conformality is formed on both the bottom and the sidewall of the groove. This shows that the preparation method of the present application can uniformly deposit a thin film material in the groove of the substrate. However, after depositing a tantalum film in the groove of the substrate using the method of Comparative Example 2, it was found that a tantalum film could not be formed in the groove of the substrate. This shows that the method of Comparative Example 2 cannot achieve the deposition of a tantalum film in an advanced groove.

[0088] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A thin film material, characterized in that: The thin film material includes tantalum, carbon and nitrogen, and the thin film material does not contain halogen, wherein the atomic percentage of the tantalum in the thin film material is greater than 70%, the atomic percentage of the carbon in the thin film material is 0.1-7%, and the atomic percentage of the nitrogen in the thin film material is 0.1-4%.

2. The film material according to claim 1, characterized in that: In the thin film material, the total atomic proportion of the carbon element and the nitrogen element is less than 10%.

3. The thin film material according to claim 1 or 2, characterized in that: The atomic ratio of the carbon element to the tantalum element is less than 0.08; the atomic ratio of the nitrogen element to the tantalum element is less than 0.

05.

4. A method for preparing a thin film material according to any one of claims 1 to 3, characterized in that: include: The thin film material is prepared by plasma deposition using organic tantalum as a precursor; wherein the organic tantalum contains carbon and nitrogen.

5. The method according to claim 4, characterized in that The organic tantalum includes at least one of Ta(NR1R2)5 or R3N=Ta(NR4R5)3, and R1 to R5 are each independently selected from C1 to C5 alkyl groups.

6. The method according to claim 4 or 5, characterized in that: A discharge gas is introduced into the plasma deposition, wherein the discharge gas includes hydrogen and argon, and a flow ratio of the hydrogen to the argon is greater than 0 and less than 3.

7. The method according to any one of claims 4 to 6, characterized in that: During the plasma deposition process, the organic tantalum is heated to 70-100° C., argon is used as a carrier gas, and the saturated vapor of the organic tantalum is loaded into the reaction chamber of the deposition equipment for a time greater than 2 seconds; a mixed gas of hydrogen and argon is used as a discharge gas, and the gas flow rates are 25-100 sccm and 0-75 sccm respectively, the discharge mode is capacitively coupled plasma, the discharge duration is 5-30 seconds, the discharge power is 50-200 W, and the frequency is less than 15 MHz.

8. An interconnect structure, characterized in that: comprising an interconnection layer, an adhesion layer and a barrier layer, wherein the adhesion layer is located between the interconnection layer and the barrier layer; The interconnection layer is a copper layer, and the adhesion layer is the thin film material according to any one of claims 1-3.

9. The interconnection structure according to claim 8, characterized in that: The thickness of the adhesion layer is less than or equal to 20 nm.

10. A chip, characterized in that: Comprising the interconnection structure as claimed in claim 8 or 9.